An Algorithm for Identifying Least Manipulable Envy-Free and Budget-Balanced Allocations in Economies with Indivisibilities - Tommy Andersson; Lars Ehlers (Lund University, School of Economics and Management, Department of Economics, 2021)
We analyze the problem of allocating indivisible objects and monetary compensations to a set of agents. In particular, we consider envy-free and budget-balanced rules that are least manipulable with respect to agents counting or with respect to utility gains. A key observation is that, for any profile of quasi-linear preferences, the outcome of any such least manipulable envy-free rule can be obtained via so-called agent-k-linked allocations. Given this observation, we provide an algorithm for identifying agent-k-linked allocations.
Keywords: C71; C78; D63; D71; D78; 330; Envy-freeness; Budget-balance; Least manipulable; Algorithm